KEAWETAN KAYU TUSAM (Pinus merkusii Jungh. et de Vr.) DAN MANGIUM (Acacia mangium Willd.) SETELAH FURFURILASI - Jamal Balfas; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan, 1995)
Two regrowth wood species, i.e. tusam (Pinus merkusii Jungh. et de Vr.) and mangium (Acacia mangium Wild.) were used in this study. Specimens measuring 25 mm x 25 mm x 50 mm and 5 mm x 25 mm x 25 mm were prepared for testing against dry-wood termite (Cryptotermes) and subteranean termite (Coptotermes) respectively. All specimens were air-dried  to approxi mately 16-18%  moisture content. One group of the specimens was further  oven - dried to reach moisture  content of  6-8%.  Furfurylation  was carried out by soaking  wood specimens for 24 hours  in a 98% fuifuryl  alcohol  solution  containing  0.35%  (v/v) of  ZnCl2  as catalyst. Furfurylated specimens were then cured at  l000C  for 48 hours.  Control and treated specimens were exposed to dry-wood and subteranean termites for 12 and 4 weeks respectively.Treated specimens revealed a weight gains of  10 to 40 % depending on size of specimens and  wood species. Speciesmens usd for testing drywood termites gained less weight than those of  subteranean termites. Tusam  specimens  markedly  showed  a  higher  weight  gain  than mangium.  Furfurylation using method 1 resulted in comparable weight gain to that of method 2. Control specimens of tusam an mangium are both encountered susceptible to dry-wood and subteranean  termite  attacts.  Tusam  had  less initial durability  against  Coptotermes  than mangium, but the wood species had a similar durability against Cryptotermess.  The modified wood with furfuryl alcohol abviously possessed an improved durability  upon the two termites. Tusam specimens gained more durability improvement than mangium.